Early results of South African men with low-risk, clinically localized prostate cancer managed with active surveillance - Dahms, Willem (University of the Free State, 2020)
Introduction and objective: To report the outcome of active surveillance (AS) offered to men with low-risk prostate cancer (PCa) at Universitas Academic Hospital in Bloemfontein, South Africa. Materials and Methods: Men with PCa with a Gleason score of 6 (3+3) on 2 needle cores or less, clinical stage cT2a and less, and prostate specific antigen (PSA) lower than 10 ng/ml were offered active surveillance. Variables such as age, self-reported ethnicity, clinical stage, PSA, PSA density (PSAD), number of positive cores and core percentage were recorded at baseline. Digital rectal examination (DRE), PSA, and PSA kinetics were recorded during follow up and repeat prostate biopsy was offered routinely within 12 months of initial diagnosis or in case of unfavourable PSA kinetics. Patients older than 70 years with lowintermediate risk were also included. Results: A total of 54 men with median age 64.8 years (range 43 years to 73 years) were surveilled for low-risk PCa for a median of 31 months (range 7 months to 126 months). Their initial median PSA was 7 ng/ml (range 1.1 ng/ml to 14.3 ng/ml). Self-reported ethnicity was African 35 (65%), European 15 (28%) mixed race 1 (2%) and other 3 (5%). Ethnicity was not associated with adverse reclassification [HR 0.5; p=0.366]. PSAD was the best predictor of reclassification [HR 1.5; p = 009]. PSA density cut-off was determined with the receiver operating curves to be 0.13ng/ml/ml which had a sensitivity of 92.9% and a specificity of 42.5% predicting favourable disease. Upgrade of Gleason score was noted in 3 (7%) and increased positive cores in 12 (27%) of the 44 men who had a repeat biopsy. Overall, 14 (26%) patients received definitive treatment for their prostate cancer while 39 (85%) remained on active surveillance. Conclusions: Based on early results, AS appears to be an appropriate management option for South African men with low risk-prostate cancer and a PSA density ≤0.13ng/ml/ml irrespective of ethnicity.
Keywords: Dissertation (M.Med Sc. (Urology))--University of the Free State, 2020; Active surveillance; Prostate cancer; Adverse reclassification; PSA density; Repeat biopsy; African men